A novel method for generating glutamatergic SH-SY5Y neuron-like cells utilizing B-27 supplement - Martin, Emily-Rose; Gandawijaya, Josan; Oguro-Ando, Asami (Frontiers in Pharmacology, 2022)
The human SH-SY5Y neuroblastoma cell line is widely used in neuroscience research as a neuronal cell model. Following differentiation to a neuron-like state, SH-SY5Y cells become more morphologically similar to neurons and form functional synapses. Previous studies have managed to differentiate SH-SY5Y cells towards cholinergic, dopaminergic and adrenergic fates. However, their application in disease modeling remains limited as other neuronal subtypes (e.g., glutamatergic, GABAergic) are also implicated in neurological disorders, and no current protocols exist to generate these subtypes of differentiated SH-SY5Y cells. Our study aimed to evaluate the use of a xeno-free version of B-27, a supplement commonly used in neuronal culture, for SH-SY5Y maintenance and differentiation. To evaluate the proliferative capacity of SH-SY5Y cells cultured in B-27, we performed growth curve analyses, immunocytochemical staining for Ki-67 and qRT-PCR to track changes in cell cycle progression. SH-SY5Y cells cultured in FBS or under serum-starved conditions were used as controls. We observed that SH-SY5Y cells show reduced growth and proliferation rates accompanied by decreased CDK6 and CDK1 expression following 4-day exposure to B-27, suggesting B-27 induces a quiescent state in SH-SY5Y cells. Importantly, this reduced growth rate was not due to increased apoptosis. As cell cycle exit is associated with differentiation, we next sought to determine the fate of SH-SY5Y cells cultured in B-27. B-27-cultured SH-SY5Y cells show changes in cell morphology, adopting pyramidal shapes and extending neurites, and upregulation of neuronal differentiation markers (GAP43, TUBB3, and SYP). B-27-cultured SH-SY5Y cells also show increased expression of glutamatergic markers (GLUL and GLS). These findings suggest that B-27 may be a non-toxic inducer of glutamatergic SH-SY5Y differentiation. Our study demonstrates a novel way of using B-27 to obtain populations of glutamatergic SH-SY5Y cells. As dysregulated glutamatergic signaling is associated with a variety of neuropsychiatric and neurodegenerative disorders, the capability to generate glutamatergic neuron-like SH-SY5Y cells creates endless disease modeling opportunities. The ease of SH-SY5Y culture allows researchers to generate large-scale cultures for high-throughput pharmacological or toxicity studies. Also compatible with the growing popularity of animal-component-free studies, this xeno-free B-27/SH-SY5Y culture system will be a valuable tool to boost the translational potential of preliminary studies requiring glutamatergic neuronal cells of human origin.